Monopoly rent and the prospects for rent relationship in state regulation - Povod, Igor N. (Journal of the Belarusian State University. Economics, 2019)
The article considers the problem of insufficient practical application of studies under the theory of rent. The solution to the problem by improving the status of monopoly rent through a change in the approach to the interpretation of this notion is proposed. Any type of rental income received by company that occupies a dominant position in the market from its main activity is among the monopoly rent. The proposed interpretation significantly increases the field of application of monopoly rent, which would in turn improves the prospects for theory of rent in the practice of state regulation. The author also propose the method for monopoly rent calculation which excludes understatement of its volume by manipulation of the employees’ salaries.
Keywords: rent; monopoly rent; rent relationship; theory of rent; method for monopoly rent calculation; state regulation